Effect of Variable Chilled Water Flow Rates and Temperature on Performance of Double Temperature Chiller with Large Temperature Glide Zeotropic Refrigerant - Liu Jian; Zhang Xiaosong (Zhileng xuebao)
To study the effect of variable chilled water flow rates and temperature on double temperature chiller with large temperature glide zeotropic refrigerant, the chiller’s performance under different conditions was investigated experimentally, including mass concentration ratio of R32/R236fa (0.4~0.6, 0.5~0.5, 0.6~0.4), chilled water flow rates change from 0.25 m3/h to 0.45 m3/h and temperature change of the high temperature chilling water. The experimental results show that the maximum and minimum COP of the unit under different flow rates is 4.17 and 3.27 respectively, this moment, the inlet and outlet water temperature of condenser are 32 ℃ and 37℃, the high-low temperature chilling water are 7 ℃ and 16 ℃. In addition, the temperature change of high temperature chilled water have obvious effect on the performance of the unit. At last, the results of this paper provide database for the application of double temperature chiller.